(3HgLI GdEfSGf aj egLI GdMjhGfs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdeqdG GdgQhj GdbGQj , J (B1014 (3g` s; (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdeaJbQ Edi HQ QHg GdHGQi Ydi Hf SdWGf eMeO GdbGQi Ef gPg GdQSGdg ajgG SdGdg eYQaI GdMjhGfGJ heG jJYdb HgG s
(3BNQgG (B:s
(3hbO NJe HgPG GdHGH ef BNQ GdcJGH HPcQ NGJe GdNdaGA dNGJe GdCfHjGA hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B65 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B178s
Keywords: (3GdcjejGA h GdWHjYjGJs